Image Steganalysis based on Pretrained Convolutional Neural Networks - Taha Ahmed I.; Tareq Hammad B.; Jamil N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Decision trees; Deep learning; Engineering education; Image classification; Learning systems; Steganography; Alexnet CNN model; CNN models; Convolutional neural network; Cover-image; Image steganalysis; Random forest classifier istego100k; Random forest classifier; Secret information; Steganalysis; Stego image; Convolutional neural networks